College Students’ Trauma and Stress Enhance Benefits of Warm-Tone Syllabus - Merry Sleigh; Donna Nelson; Alyssa Nelson; Meridee Ritzer (Journal of Effective Teaching in Higher Education)
A high percentage of students enter college with prior trauma, and trauma-informed practices are increasingly recognized as valuable in higher education. We examined if the tone of a syllabus would interact with levels of trauma or stress to impact participants’ perceptions of the instructor, willingness to seek help, and self-efficacy. We tested a 2 (tone: warm vs. cold) X 2 (trauma: low vs. high) experimental design and a 2 (tone: warm vs. cold) X 2 (stress: low vs. high) experimental design. College students read a syllabus, varying in tone, and then indicated their willingness to communicate with the instructor, as well as perceptions of their classroom self-efficacy and instructor attributes. Results revealed that in the high trauma condition, students attributed the most positive attributes to the warm-syllabus instructor and the most negative attributes to the cold-syllabus instructor. Student trauma did not interact with syllabus tone to predict perceived self-efficacy or willingness to communicate. Student stress did not interact with syllabus tone to predict instructor attributes or perceived self-efficacy; however, in the warm condition, high stress students revealed the greatest willingness to communicate with the instructor. The use of a warm syllabus as a tool to create a supportive learning environment benefits all college students, but particularly those experiencing high levels of stress or trauma.